The Effectiveness of Using Artificial Intelligence/Robots in Virtual Learning during the COVID 19 Pandemic - Dahlan, Achmad (Indonesian Journal of Curriculum and Educational Technology Studies, 2023)
This research investigates the impact of integrating Artificial Intelligence (AI) into education during the Covid-19 pandemic, examining AI's dual role as a transformative force and a potential threat. Focused on the changing landscape of the teaching profession due to technology, particularly AI, the study aims to evaluate AI's contributions to virtual learning, analyze its advantages and threats, and propose optimal implementation solutions. Utilizing a qualitative hermeneutic phenomenological approach, insights were gathered from 20 UIN Walisongo Semarang students in Indonesia. Results emphasize AI's versatile applications, highlighting positive impacts on learning quality, personalization, and practical opportunities. However, attention is needed for addressing negative consequences, including technology addiction, social issues, mental health concerns, reduced creativity, and high implementation costs. The study underscores the crucial role of teachers and envisions a collaborative future where AI and human educators synergize to enhance critical thinking and social interaction, advocating for a balanced approach to AI integration in education. Abstrak Penelitian ini mengkaji dampak dari implementasi Kecerdasan Buatan (Artificial Intelligence/AI) dalam dunia pendidikan selama pandemi Covid-19, dengan meninjau peran ganda AI sebagai kekuatan transformatif dan potensi ancaman. Berfokus pada perubahan paradigma profesi pengajar akibat teknologi, khususnya AI, penelitian ini bertujuan untuk mengevaluasi kontribusi AI dalam pembelajaran virtual, menganalisis keuntungan dan ancamannya, serta mengusulkan solusi implementasi yang optimal. Dengan menggunakan pendekatan fenomenologi hermeneutik kualitatif, informasi diperoleh dari 20 mahasiswa UIN Walisongo Semarang di Indonesia. Hasil penelitian menekankan aplikasi AI yang serbaguna, menyoroti dampak positif pada kualitas pembelajaran, personalisasi, dan peluang praktis. Namun, perhatian diperlukan untuk mengatasi dampak negatifnya, termasuk kecanduan teknologi, masalah sosial, masalah kesehatan mental, berkurangnya kreativitas, dan biaya implementasi yang tinggi. Studi ini menggarisbawahi peran penting guru dan membayangkan masa depan kolaboratif di mana AI dan pendidik manusia bersinergi untuk meningkatkan pemikiran kritis dan interaksi sosial, mengadvokasi pendekatan yang seimbang untuk integrasi AI dalam pendidikan.